UX (USER EXPERIENCE) EVALUATION OF THE OPENLEARNING SYSTEM AT UNIVERSITAS MUHAMMADIYAH SURAKARTA USING HEURISTIC EVALUATION AND USABILITY TESTING - Imana, Afifah Ghaisani; Nugroho , Yusuf Sulistyo (Jurnal Teknik Informatika (Jutif), 2023)
Since the COVID-19 pandemic in 2020, the learning process at the University of Muhammadiyah Surakarta (UMS) has been carried out online using the OpenLearning platform. The use of OpenLearning media has provided an easy learning process for both lecturers and students. Although there are many conveniences and benefits offered, usability problems still arise, for example, there is no distinction between courses that have ended and those that are still active, the "Edit Page Header" feature on student users, and misperceptions in the progress bar in the Course menu. In addition, previous research has evaluated the UMS OpenLearning platform using the System Usability Scale (SUS) technique and scored 61 (grade scale D) and indicates that the system is well received. To identify more detailed problems related to user experience (UX) for the OpenLearning system applied at UMS, it is necessary to evaluate the UX with the other approaches. In this study, the Heuristic Evaluation method based on 10 principles of Heuristic and Usability Testing based on 5 Usability criteria are implemented to evaluate. The results of this study are a system prototype according to the results of heuristic evaluation. The prototype was evaluated using SUS method on 380 respondents. The SUS calculation yields a value of 69, which indicates that the system is classified to the grade scale category D. This insignificant increase in the SUS score indicates that the UX improvements have not been optimally related to usability due to some factors such as the complexity of the system when used, inconsistencies, and the need for users to adapt to using the system. This finding can be considered by the system development team to fix the weaknesses so as to create an online learning platform with a better UX.